Pengaruh Model Pembelajaran Contextual Teaching and Learning Terhadap Keterampilan Berpikir Kreatif Siswa Kelas VII pada Tema Lingkunganku Tercemar - Ahmad Fikriyani; Lukman Nulhakim; Annisa Novianti Taufik (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to analyze the effect of the Contextual Teaching and Learning (CTL) model on students' creative thinking skills in science learning at the junior high school level. The method used in this study is a quasi-experimental design with a non-equivalent control group design. This study involved all seventh-grade students at MTs Negeri 1 Serang, consisting of 10 classes. The research sample was randomly selected, with Class VII A as the experimental group using the Contextual Teaching and Learning model, while Class VII E served as the control group using the Discovery Learning model. Data collection was carried out through creative thinking skill essay tests and non-test observations of students' creative thinking abilities. The test instrument used was validated and tested for reliability. The results showed that the Contextual Teaching and Learning model significantly influenced the improvement of students' creative thinking skills. Although the data distribution was not normal, hypothesis testing using statistical tests indicated significant differences between the pretest and posttest results. Thus, the Contextual Teaching and Learning model can be an effective alternative to enhancing students' creative thinking skills in understanding scientific concepts, particularly concerning environmental pollution issues. Keywords: Contextual Teaching and Learning, Creative Thinking Skills, Environmental Pollution, Integrated Science